Water quality monitoring in the Paul do Boquilobo Biosphere Reserve - Baptista, C. (2021)
The Paul do Boquilobo is an important wetland ecosystem classified by Unesco as a MAB Biosphere reserve also awarded Ramsar site status, representing one of the most important habitats for the resident nesting colony of Cattle Egret (Bulbucus ibis). Yet owing to its location, it suffers from human induced impacts which include industrial and domestic effluent discharges as well as agricultural land use which have negatively impacted water quality. The current study reports the results obtained from the introductory monitoring programme of surface water quality in the Nature Reserve to emphasize the detrimental impact of the anthropogenic activities in the water quality of such an important ecosystem. The study involved physicochemical and biotic variables, microbial parameters and biological indicators. Results after 3 years of monitoring bring to evidence a poor water quality further impaired by seasonal patterns. Statistical analysis of data attributed water quality variation to 3 main parameters – pH, dissolved oxygen and nitrates, indicating heavy contamination loads from both organic and agricultural sources. Seasonality plays a role in water flow and climatic conditions, where sampling sites presented variable water quality data, suggesting a depurative function of the wetland.